2012
DOI: 10.1111/jop.12031
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory methods and biomarkers in the evaluation of bisphosphonate effects on body tissues: a literature review

Abstract: Bisphosphonates are extensively used to treat bone metabolism disorders; meanwhile, these drugs have important side effects such as jaw osteonecrosis and femoral fracture. Therefore, studies have been conducted aimed at better understanding their mechanism of action and determining a course of action to avoid these side effects. We present here a literature review focusing on the laboratory methods available for investigating bisphosphonate effects on body tissues. There are many different methods available fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 116 publications
(189 reference statements)
0
2
0
1
Order By: Relevance
“…Some authors agree and others disagree with these concepts of drug holiday and CTX defended by Marx et al . According to Baim and Miller, serum CTX as a predictor of BRONJ has yet to receive rigorous evidence‐based validation, and there are currently insufficient data to support using CTX levels to guide the modification of bisphosphonate therapy in such a way as to minimise the risk of developing BRONJ.…”
Section: Management Of Patients Under Alendronate Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors agree and others disagree with these concepts of drug holiday and CTX defended by Marx et al . According to Baim and Miller, serum CTX as a predictor of BRONJ has yet to receive rigorous evidence‐based validation, and there are currently insufficient data to support using CTX levels to guide the modification of bisphosphonate therapy in such a way as to minimise the risk of developing BRONJ.…”
Section: Management Of Patients Under Alendronate Therapymentioning
confidence: 99%
“…On the other hand, there are studies that have shown that CTX, in spite of its limitations, can provide important information for assessing oral bisphosphonate users who need to undergo oral surgery 4,[56][57][58][59][60]69 . A study evaluated a total of 348 patients on the basis of fasting morning CTX, where 215 patients were taking long-term oral bisphosphonates, most of them alendronate for osteoporosis treatment.…”
Section: Oral Surgery Serum C-terminal Telopeptide Test (Serum Ctx) mentioning
confidence: 99%
“…Assim, a inibição do osteoclastos diminui a angiogênese no microambiente ósseo (CACKOWSKI et al, 2010). Os efeitos antiangiogênicos dos BF, a inibição da proliferação, migração e adesão de células endoteliais, bem como a indução de diminuição do fluxo sanguíneo em ossos longos têm sido relatados (KAPITOLA; ZAK, 1998;VASCONCELOS et al, 2013). Altas doses intravenosas de ZA foram capazes de induzir a diminuição na densidade dos pequenos vasos e diminuição do comprimento da rede vascular na calvária de ratos (VIEILLARD et al, 2010).…”
Section: Investigaram O Efeito Do Az Em Doses Oncológicas E Dounclassified